The alternative approach of low temperature-long time cooking on bovine semitendinosus meat quality - Ismail, Ishamri (Asian-Australas J Anim Sci, 2019)
OBJECTIVE: This study aimed to elucidate whether innovative sous vide treatment has a significant influence on the beef semitendinosus muscle as compared to common sous vide treatment and traditional cooking. METHODS: The innovative sous vide treatments were cooked at 45°C and 65°C for 6 h (SV45–65), common sous vide treatment at 45°C and 65°C for 3 h (SV45 and SV65) and traditional cooking at 75°C for 30 min (CON75). Water loss and cooking loss, as well as the physical properties (color and shear force) and chemical properties (protein and collagen solubility) of the treated meat, were investigated. RESULTS: The results obtained indicated that the innovative sous vide with double thermal treatment (SV45–65) and cooked with air presence (CON75) resulted to lower a* and higher b* values, respectively. The water loss and cooking loss increased when temperature increased from 45°C to 65°C, and lower water loss was recorded in SV45 and CON75. These samples presented higher water content and revealed strong correlation to protein solubility. Warner-Bratzler shear force (SF) analysis showed the marked interaction between cooking temperature and time. Sample cooked at a high temperature (CON75) and a long period (SV45–65) showed a significantly lower value of SF than sample SV65 (p<0.05). Interestingly, there was no difference in SF values between SV45–65 and CON75. CONCLUSION: The innovative sous vide treatment with double thermal effect appears an attractive cooking method as compared to common sous vide and traditional cooking method, as it has a potential for improving tenderness values of cooked beef semitendinosus muscle.